Multi-Level Design of Process-Oriented Enterprise Information Systems - Frank, Ulrich; Clark, Tony (Enterprise Modelling and Information Systems Architectures (EMISAJ), 2022)
This paper presents prototypical multi-level models of two uses cases. They comprise models of business processes and of models that represent the context required to execute a business process. On the one hand, the context consists of the organizational units that are responsible for the execution of processes. They are represented by a model of organizational structures. On the other hand, the context includes the artifacts that are needed or manipulated by processes. The models serve to demonstrate the specific power of multi-level modeling. First, they integrate models on higher levels, which correspond to domain-specific modeling languages, with those on lower levels. In addition, models are supplemented with objects on L0 to demonstrate how these can be integrated. The models are executable without the need to generate code, since models and corresponding program code share the same representation, thus demonstrating the possibility of advanced application system architectures, which allow users to navigate a comprehensive representation of the system they work with at runtime. The presentation of the models is supplemented with a general evaluation of multi-level concepts. The design of the models was inspired by the EMISA process challenge. Therefore, they are evaluated against the requirements defined with the challenge. In addition, a challenge is discussed that goes beyond the challenge, that is, the design of multi-level models of behavior.